Counsellor Learner Style: A Variable in Career Choice - Torbit, Gary (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this study was to investigate the assumptions ( Kolb & Plovnick. 1976) that people chose careers which are consistent with their learning styles and are further shaped to fit the learning norms of the career once they are in it. A group of 35 counsellor trainees completed Kolb's (1976) Learning Style Inventory by indicating their "preferred" learning style, and subsequently, their perceptions of "counsellor" learning style. The results supported the assumptions and were discussed with respect to the implications for counsel- lor training methodology and client/counsellor problem-solving behaviour.